Efficacy of Azithromycin in the Treatment of Childhood Typhoid Fever - Islam, MN; Rahman, ME; Rouf, MA; Islam, MN; Khaleque, MA; Siddika, M; Hossain, MA (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2007 Jul;16(2): 149-153 The abstract of this article is available on the PubMed website